1998
DOI: 10.1021/om970917f
|View full text |Cite
|
Sign up to set email alerts
|

Metallacycle Expansion by Alkyne Insertion. Chemistry of a New Family of Ruthenium Organometallics

Abstract: Acetylene and phenylacetylene reacts with carbonylchloro[4-methyl-6-((R-imino)methyl)phenolato-C,O]bis(triphenylphosphine)ruthenium(II), Ru(RL 1 )(PPh 3 ) 2 (CO)Cl (3), affording the inserted product carbonylchloro[2-vinyl-4-methyl-6-((R-imino)methyl)phenolato-C,O]bis-(triphenylphosphine)ruthenium(II), Ru(RL 2 ,X)(PPh 3 ) 2 (CO)Cl ( 4), in virtually quantitative yield. The X-ray structures of 4b (R ) X ) Ph) and 4g (R ) Et, X ) H) have revealed the presence of distorted-octahedral RuC 2 P 2 ClO coordination sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
2
30
1
Order By: Relevance
“…This peak disappeared after shaking the NMR sample solution in D 2 O, which supported the presence of an exchangeable proton in the -OH functional group ( Figure S14). [11,23] These data supported a dissociation of the Ru-O Ph bond during NO coordination in 1a.…”
Section: Spectroscopic Studiesmentioning
confidence: 55%
“…This peak disappeared after shaking the NMR sample solution in D 2 O, which supported the presence of an exchangeable proton in the -OH functional group ( Figure S14). [11,23] These data supported a dissociation of the Ru-O Ph bond during NO coordination in 1a.…”
Section: Spectroscopic Studiesmentioning
confidence: 55%
“…This complex could be described by the zwitterionic structure 38, featuring an NH⋅⋅⋅O hydrogen bond. [67] Scheme 16 Milstein and co-workers reported that a non-zwitterionic Pt IV complex produced by intramolecular C-H activation of a neutral Pt II complex undergoes spontaneous stabilization through intramolecular proton-transfer to a pendant amino group to give the zwitterionic Pt II complex 39 (Scheme 17). [68] Scheme 17…”
Section: ⋅⋅⋅mentioning
confidence: 99%
“…We are scrutinizing the reactivity of these compounds. It has been found that different alkynes undergoes facile insertion into the Ru-C bond of the fourmembered ruthenium metallacycles leading to two carbon expansion [20][21][22] whereas the osmium analogue remains unreactive. Upon treatment with isonitrile ruthenium system undergoes halide substitution as well as insertion into the Ru-O bond and the resultant product then exhibits aryl migration and C-C bond formation [23,24] while in case of osmium system isonitrile simply displaced bromide ligand furnishing the cationic complexes which are isolated as salts [25].…”
Section: Introductionmentioning
confidence: 99%